The relationship between the functional status of the extremities and “core” stabilization in women with fibromyalgia - Sinem Kuru; Bilge Basakci Calik; Elif Gur Kabul; Murat YIGIT (Rheumatology)
Introduction The aim of this study was to examine the relationship between the functional status of the extremities and “core” stabilization in women with fibromyalgia (FM).